On the nature of high-amplitude propagating pressure waves in the human colon - Milkova, Natalija; Parsons, Sean P.; Ratcliffe, Elyanne; Huizinga, Jan D.; Chen, Ji-Hong (American journal of physiology: Gastrointestinal and liver physiology, 2020)
Characterization of high-amplitude propagating pressure waves (HAPWs or HAPCs) plays a key role in diagnosis of colon dysmotility using any type of colonic manometry. With the introduction of high-resolution manometry, more insight is gained into this most prominent propulsive motor pattern. Here, we use a water-perfused catheter with 84 sensors with intervals between measuring points of 1 cm throughout the colon, for 6–8 h, in 19 healthy subjects. The catheter contained a balloon to evoke distention. We explored as stimuli a meal, balloon distention, oral prucalopride, and bisacodyl injection, with a goal to optimally evoke HAPWs. We developed a quantitative measure of HAPW activity, the “HAPW Index.” Our protocol elicited 290 HAPWs. 21% of HAPWs were confined to the proximal colon with an average amplitude of 75.3 ± 3.3 mmHg and an average HAPW Index of 440 ± 58 mmHg·m·s. 29% of HAPWs started in the proximal colon and ended in the transverse or descending colon, with an average amplitude of 87.9 ± 3.1 mmHg and an average HAPW Index of 3,344 ± 356 mmHg·m·s. Forty-nine percent of HAPWs started and ended in the transverse or descending colon with an average amplitude of 109.3 ± 3.3 mmHg and an average HAPW Index of 2,071 ± 195 mmHg·m·s. HAPWs with and without simultaneous pressure waves (SPWs) initiated the colo-anal reflex, often abolishing 100% of anal sphincter pressure. Rectal bisacodyl and proximal balloon distention were the most optimal stimuli to evoke HAPWs. These measures now allow for a confident diagnosis of abnormal motility in patients with colonic motor dysfunction. NEW & NOTEWORTHY High-amplitude propagating pressure waves (HAPWs) were characterized using 84 sensors throughout the entire colon in healthy subjects, taking note of site of origin, site of termination, amplitude, and velocity, and to identify optimal stimuli to evoke HAPWs. Three categories of HAPWs were identified, including the associated colo-anal reflex. Proximal balloon distention and rectal bisacodyl were recognized as reliable stimuli for evoking HAPWs, and a HAPW Index was devised to quantify this essential colonic motor pattern.